MITgcm model setup and output for "Development of adjoint-based ocean state estimation for the Amundsen and Bellingshausen Seas and ice shelf cavities using MITgcm/ECCO" - Nakayama, Yoshihiro (10148865) (2021)
MITgcm model setup and output for "Development of adjoint-based ocean state estimation for the Amundsen and Bellingshausen Seas and ice shelf cavities using MITgcm/ECCO" (Contents) Here it contains code.zip (code to run this simulation) input.zip (input file required for this simulation) run478it20.zip (output of ocean state estimates for iteration 20) (How to compile) To run this simulation, mkdir build cd build /nobackup/ynakaya2/MITgcm/tools/genmake2 -rootdir=/nobackup/ynakaya2/MITgcm -of ./code2/linux_amd64_ifort+mpi_ice_nas -mpi -mods ./code2/ make depend make adall (How to submit a job) script_run470_mitgcmad.csh is used to submit a job for running simulation. script_optim478 is used for optimization jobs. For more info please send an email to Yoshihiro.Nakayama@lowtem.hokudai.ac.jp